2014
DOI: 10.7202/1021541ar
|View full text |Cite
|
Sign up to set email alerts
|

Aider, s’aider, s’entraider : expériences de femmes travailleuses du sexe de rue et utilisatrices de drogues par injection dans une recherche-action participative visant la prévention du VIH

Abstract: L’intervention par les pairs est appelée à occuper une place grandissante parmi les initiatives pour prévenir l’acquisition/transmission du VIH. Une telle stratégie requiert nécessairement la participation des personnes et des groupes concernés. Or, l’expérience de la participation a été très peu documentée chez des femmes travailleuses du sexe de rue et utilisatrices de drogues injectables (TSR-UDI) impliquées dans une intervention par les pairs. Les résultats de l’analyse qualitative du Projet LUNE, une rech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Therefore, people with lived and living experiences of drug use are invaluable allies to shape and deliver HR services such as naloxone programs (Faulkner-Gurstein, 2017) as well as shelters, housing, or HIV and HCV treatment programs (Greer et al 2021). People who use drugs may derive many benefits from partaking in peer-led activities, such as raised self-esteem, feelings of usefulness (Crabtree et al, 2015; Greer et al, 2021; Kerr et al, 2006), acquisition of new knowledge and skills, and greater structuring of their daily lives (Labbé et al, 2013). A study with 874 PWID from Vancouver, Canada found that if they had the choice, 48% of participants would rather take a low threshold job than resort to other money-generating activities such as panhandling, drug dealing, or sex work (Debeck et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, people with lived and living experiences of drug use are invaluable allies to shape and deliver HR services such as naloxone programs (Faulkner-Gurstein, 2017) as well as shelters, housing, or HIV and HCV treatment programs (Greer et al 2021). People who use drugs may derive many benefits from partaking in peer-led activities, such as raised self-esteem, feelings of usefulness (Crabtree et al, 2015; Greer et al, 2021; Kerr et al, 2006), acquisition of new knowledge and skills, and greater structuring of their daily lives (Labbé et al, 2013). A study with 874 PWID from Vancouver, Canada found that if they had the choice, 48% of participants would rather take a low threshold job than resort to other money-generating activities such as panhandling, drug dealing, or sex work (Debeck et al, 2011).…”
Section: Discussionmentioning
confidence: 99%